Considerations for the Study on the Relationships Between Education and Development - Cabugueira, Artur Carlos Crespo Martins (2002)
In this article we develop some aspects as regards the relationshipsbetween education and development, with particular emphasis beinggiven to the issues related to human capital. We start to review the mainideas and theories about the subject, from the Mercantilists to thecontemporary authors, pointing out specially the emergence of the humancapital theory in the 60’s. On one hand, we present the reasons for theappearance of this theory; we describe the arguments used by theirsupporters, namely those related to the contributions from which the newneoclassical models of growth have emerged. According to these newmodels the significant factor of economic growth is endogenousinnovation, being this innovative activity produced in the interior of theeconomy and itself influenced by providing economy with human capital.On the other hand, we present the reasons why some authors refuse oraccept conditionally the importance of human capital for the economicdevelopment. Therefore, we present current criticisms as well as refer therequirements and conditions often suggested and considered crucial inorder for the education to become a factor, among many others, that influences positively on behalf of the society. To conclude, we analysedall the opinions, giving our own point of view on the area underdiscussion.